1989
DOI: 10.2354/psj.5.36
|View full text |Cite
|
Sign up to set email alerts
|

ABO Antigens in Red Cells and Digestive Organs of Non-human Primates

Abstract: Blood group A, B and H antigens on red cells of non-human primates were examined by direct hemagglutination reaction, antibody absorption and heat elution tests. ABH substances on red cells from prosimians, New World and Old World monkeys were detected only by elution test with human anti-A, anti-B and chicken immune anti-H antibodies and their activities were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…1 B). The + 5.8-kb site is conserved among human, chimpanzee, gorilla, and gibbon, showing similar expression of A- and B-antigens on RBCs 13 , whereas it is not conserved in monkeys such as crab-eating macaque, rhesus macaque and marmoset, in which the A- and B-antigens are expressed only slightly on RBCs. On the other hand, the + 22.6-kb site is conserved among humans and those primate species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 B). The + 5.8-kb site is conserved among human, chimpanzee, gorilla, and gibbon, showing similar expression of A- and B-antigens on RBCs 13 , whereas it is not conserved in monkeys such as crab-eating macaque, rhesus macaque and marmoset, in which the A- and B-antigens are expressed only slightly on RBCs. On the other hand, the + 22.6-kb site is conserved among humans and those primate species.…”
Section: Resultsmentioning
confidence: 99%
“…Similar reduced reactivity of RBCs with anti-A or anti-B antibody is observed in non-human primates. Studies using routine anti-A and anti-B reagents have shown that agglutination of RBCs in apes such as chimpanzees, gorillas, orangutans, and gibbons is similar to that of human subgroups such as A int or B int 13 , 14 . A int erythrocytes have lower amounts of A-antigen than A 1 erythrocytes and higher amounts than A 2 erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation